A Project Report on Wood Flex'ure Testing Machine - ADHAVAN S, PRADEEP KUMAR, RADHAKRISHNAN A V, VENUGOPAL V, MANOJ KUMAR K and MURALI V S (1993)
INTERNAL GUIDE: HARISH KUMAR D, MVJCE
Keywords: Wood Flex'ure Testing Machine